STRATEGI MENGATASI KONFLIK DALAM HUBUNGAN ROMANTIS ADAPTASI DAN VALIDASI THE ROMANTIC PARTNER CONFLICT SCALE - Julaibib Julaibib; Putri Saraswati (Universitas Muhammadiyah Gresik, 2025)
Background: Conflicts do not only occur in everyday life, but also in romantic relationships. Dissatisfaction, separation, or even death will be the result of conflict in romantic relationships if not addressed early or faced in a positive way. Seeking help from a counselor is one of the beneficial methods for dealing with conflict. However, one obstacle in the assessment process is the unavailability of measuring instruments that can be used by counselors. Objective: This study aims to adapt and validate The Romantic Partner Conflict Scale (RPCS) into Indonesian language and culture. Method: The RPCS adaptation was conducted using the backward translation technique. Evidence validity based on test content using Aiken's V and based on internal structure using CFA was used. The respondents in this study were 644 people. Result: The results of the adaptation of the RPCS into Indonesian language and culture show that the RPCS items (total of 37 items, 2 dropped) can measure each dimension of the RPCS and are easily understood by respondents. The validation results show the availability of validity evidence based on test content and internal structure. Conclusion: The Indonesian version of the RPCS can be used by counselors for assessment purposes or by researchers for research purposes.